Is Cryptocurrency Risky as An Investment Instrument? Analysis of Return and Risk with A Comparison of Sharia Stocks - Ahmadi, Hanif (IJIBE (International Journal of Islamic Business Ethics), 2023)
Cryptocurrency instruments show an increase in the number of investors in Indonesia, the increase in cryptocurrency investors is even bigger than the number of stock investors in the Indonesian capital market, even though stock investors also increase. The increase in stock and cryptocurrency investors is an indication that the investment climate in Indonesia is starting to improve, this must be accompanied by increased financial literacy regarding the returns and risks of an investment instrument, this research is important considering that understanding the returns and risks of an investment instrument is crucial in the decision making. The test in this study uses a descriptive statistics and independent sample t-test, if the sample does not meet the requirements of the parametric statistical test, it will use the nonparametric statistical test Mann Whitney Test, which aims to determine whether there is a difference in return and risk of cryptocurrencies and sharia stock prices for the period January 2015 to October 2021. This study finds that there are significant differences in the returns and risk of cryptocurrencies and Sharia Stocks. Based on descriptive statistics, the standard deviation of cryptocurrency returns is greater than the standard deviation of Sharia stocks, indicating that cryptocurrency risks are higher than Sharia Stocks.